Examining GenAI readiness and behavioral intention of adult learners: a PLS-SEM and IPMA approach - Chan, Josephine Ie Lyn; Tan, Saw Fen; Chew, Meng Cheng (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the current rapidly changing technological landscape, emerging technologies such as generative artificial intelligence (GenAI) continue to disrupt adult learners’ preparedness for the AI-driven future in the workplace and in society. This study aimed to explore the factors of adult learners’ behavioral intention towards adopting GenAI. A quantitative approach was used where a self-administered online survey was randomly distributed to existing adult learners at an open and distance learning (ODL) institution in Malaysia. There were 484 responses, however, due to straightlining and outlier issues, only 460 were usable. Data analysis used SPSS version 28 for data cleaning and descriptive statistics, and SmartPLS 4 to perform partial least squares structural equation modelling (PLS-SEM) and the assessment of importance-performance matrix analysis (IPMA). The findings indicated that GenAI readiness constructs of ability and ethics positively predict adult learners’ intention to adopt GenAI. Management of the university should address the performance gap in ability, maintain ethical awareness, and improve the performance of vision and cognition.